دراسة مرض الساق الأسود في حقول التبغ البلدي في محافظة طرطوس - حسن محمود; علاف عصام; حسن طارق (Latakia University Journal -Biological Sciences Series, 2019)
جُمعت خلال المسح الحقلي نباتات تبغ الصنف البلدي ( شك البنت ) تحمل أعراض مشابهة لمرض الساق الأسود من تسعة مواقع في محافظة طرطوس. وأشارت نتائج عملية العزل والفحص المجهري, وقياس أبعاد الأكياس البوغية, واختبار القدرة الإمراضية أن المسبب الرئيس لهذه الأعراض هو الفطر Phytophthora parasitica (Dast.) var nicotianae (B.de Haan) Tucker وهو أول تسجيل للمرض في سورية. وأشارت نتائج المسح الحقلي في مواقع الدراسة خلال موسمي الدراسة 2007 و2008 إلى تركّز الإصابة على التبغ المزروع على الارتفاعات المتوسطة, إذ تراوح متوسط نسبة الإصابة ما بين 7.18 %, 11.5% في كلٍ من الكريم, المجيدل على التوالي. ومتوسط شدّة الإصابة 2.13% في كلٍ من الكريم والمجدل و3.75% في المجيدل. وسجلت فروق معنوية بين المواقع ذات الارتفاعات المتوسطة كالمجيدل وكاف الحمام ووادي السقي وباقي المواقع, وقد يعزى ذلك إلى عدد من العوامل منها الحرارة المناسبة لنمو المرض وتطوره . During field survey in tobacco (Al-Balady variety) fields, tobacco samples of black shank suggestive symptoms were collected from nine locations in Tartous governorate. Results of isolation and microscopic tests of pathogen, measurements of sporangia, and pathogenicity tests proved that the causal agent of these symptoms is Phytophthora parasitica (Dast.)var. nicotianae (B.de Haan) Tucker. And this is the first record of this disease in Syria. Survey results concerning previous locations, during 2007 and 2008 growing seasons, showed the concentration of the black shank disease in the medium heights with average of infection percentage 7.18%, 11.5% in Al-Kraem , and Al-Mojaedle respectively. The average of infection was about 2.13% in each of Al-Majdel and Al-Kraem and 3.75% in Al-Mojaedle. Significant differences between these heights like Al-Mojaedle, Kaf Al-Hamam, and Wady Al-Saky and others were recorded. We may relegate these results to some factors, such as the suitable temperature and moisture for the disease to grow and develop.